New approaches to the characterization of carbon paste electrodes using the ohmic resistance effect and qualitative carbon paste indexes - Mikysek, Tomás; Svancara, Ivan; Kalcher, Kurt; Bartos, Martin; Vytras, Karel; Ludvík, Jirí (Analytical chemistry, 2009)
In this article, some new approaches to characterize the carbon paste mixtures and the respective carbon paste electrodes (CPEs) are presented, discussed, and critically evaluated. Particular attention has been paid to the changes of the ohmic resistance, relative to the dependence on composition of the CPE, the materials used, the time, and the position of storage. Four types of carbon pastes were examined, and for the interpretation of experimental data, a new simple model of "close-packing of spheres" has been applied. This model resembles the percolation theory for solid matter. In our case, however, it is possible to explain not only the "bent" or "broken" shape of the dependence of the electrode resistance upon the binder:carbon ratio and the corresponding electrochemical current response, but also differences caused by various material used and three various effects observed during the electrode aging. Furthermore, the report presents the significance of practical utilization of the recently introduced carbon paste index (denoted as chi(CPE)), which is a qualitative hitherto unused factor based on the evaluation of cyclic voltammograms for standard redox systems (e.g., [Fe(CN)(6)](3-/4-)) and specifying the electrochemical properties of a CPE. Some problems connected with homogeneity and stability of carbon pastes, their handling, storage, or eventual aging effects are also discussed.
Keywords: elektrody; Electrodes; elektrická impedance; Carbon; uhlík; Electric Impedance; Electrochemistry; elektrochemie